2020
DOI: 10.1186/s12284-020-00385-5
|View full text |Cite
|
Sign up to set email alerts
|

OsSLC1 Encodes a Pentatricopeptide Repeat Protein Essential for Early Chloroplast Development and Seedling Survival

Abstract: Background: The large family of pentatricopeptide repeat (PPR) proteins is widely distributed among land plants. Such proteins play vital roles in intron splicing, RNA editing, RNA processing, RNA stability and RNA translation. However, only a small number of PPR genes have been identified in rice. Results: In this study, we raised a mutant from tissue-culture-derived plants of Oryza sativa subsp. japonica 'Zhonghua 11', which exhibited a lethal chlorosis phenotype from germination to the third-leaf stage. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 62 publications
1
21
0
Order By: Relevance
“…Defective or damaged PPR proteins, therefore, usually lead to very severe phenotypes, such as embryo development delay, pigmentation defect, and abnormal chloroplast biogenesis [ 23 , 24 , 25 ]. Focusing on only chloroplasts, defective and damaged PPR proteins lead to several phenotypes: pale-yellowish, grana thylakoid formation altered, chlorophyll synthesis hindered, and even severe defects in photosynthesis [ 26 , 27 ]. In conclusion, PPR proteins can influence chloroplast biogenesis or development by diverse action modes and functional types.…”
Section: Introductionmentioning
confidence: 99%
“…Defective or damaged PPR proteins, therefore, usually lead to very severe phenotypes, such as embryo development delay, pigmentation defect, and abnormal chloroplast biogenesis [ 23 , 24 , 25 ]. Focusing on only chloroplasts, defective and damaged PPR proteins lead to several phenotypes: pale-yellowish, grana thylakoid formation altered, chlorophyll synthesis hindered, and even severe defects in photosynthesis [ 26 , 27 ]. In conclusion, PPR proteins can influence chloroplast biogenesis or development by diverse action modes and functional types.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the Gmpgl2 mutant, the expression of NEP and PEP increased in developmental stages S1 and S2. Recently, this kind of changes has been observed in the knockout of SLC1 gene, which encodes a P subgroup of PPR protein in rice ( Lv et al, 2020 ). In slc1 mutant, the transcript levels of 3 chloroplast ribosomal RNAs and 16 chloroplast development-related and photosynthesis-related genes were also significant increased.…”
Section: Discussionmentioning
confidence: 99%
“…In slc1 mutant, the transcript levels of 3 chloroplast ribosomal RNAs and 16 chloroplast development-related and photosynthesis-related genes were also significant increased. This phenomenon was attributed to preclude the intron splicing of rps16 in the slc1 mutant, which blocked the post-transcriptional processing and translation of rps16 , and failed to assemble the normal 70S ribosomes ( Lv et al, 2020 ). In our study, the rps16 -56313 was the unique editing site, which was completely abolished in the Gmpgl2 mutant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We analyzed the nine gene annotations in the qPAA7 interval. According to the results of the previous studies, LOC_Os07g41220,LOC_Os07g41230, and LOC_Os07g41280 showed the PCD or accumulation of ROS functions, and the other six candidate genes did not show similar functions (Zhang L. et al, 2015;Xiao et al, 2018;Lv et al, 2020). LOC_Os07g41220 was annotated as a peptidase aspartic family protein, and studies have found that aspartic proteases are related to plant development and cell death (Niu et al, 2013).…”
Section: Discussionmentioning
confidence: 99%